1999
DOI: 10.1046/j.1537-2995.1999.39101045.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance of four microtube column agglutination systems in the detection of red cell alloantibodies

Abstract: The sensitivity of all four microtube column systems in the detection of clinically significant red cell alloantibodies was similar and was markedly superior to that of the tube LISS-IAT. An individual cost-benefit analysis should be performed in every institution to decide whether a microtube column system should be applied. If so, the antibody screen in the microtube column agglutination system should ideally be performed in advance of the crossmatch to provide time to screen for compatible units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 12 publications
6
32
1
1
Order By: Relevance
“…We found that DATs by gel microcolumn assays were more sensitive than those by tube agglutination assays for detecting IgG on patient samples and D‐sensitized RBCs. This is consistent with several other studies that have found the IAT by gel microcolumn assays to be more sensitive than the IAT by tube agglutination assays at detecting IgG antibodies 3,4,7–9 and with two studies that found the DAT by gel microcolumn assay to be more sensitive at detecting RBC‐bound IgG than the DAT by tube agglutination assay 10,11 …”
Section: Discussionsupporting
confidence: 91%
“…We found that DATs by gel microcolumn assays were more sensitive than those by tube agglutination assays for detecting IgG on patient samples and D‐sensitized RBCs. This is consistent with several other studies that have found the IAT by gel microcolumn assays to be more sensitive than the IAT by tube agglutination assays at detecting IgG antibodies 3,4,7–9 and with two studies that found the DAT by gel microcolumn assay to be more sensitive at detecting RBC‐bound IgG than the DAT by tube agglutination assay 10,11 …”
Section: Discussionsupporting
confidence: 91%
“…In our report we compared the automatic Immucor Galileo system with the established DiaMed typing system (gel centrifugation test) using standard manual testing and our inhouse solution with a semi-automated system configuration in terms of the detection of human blood typing, antibody screening and cross-match testing. It is generally accepted that gel technology is a highly sensitive method [15,16]. Our results indicate that the Immucor Galileo system performs routine blood bank tests with the same accuracy like standard manual and semi-automated methods.…”
Section: Discussionsupporting
confidence: 51%
“…The discrepancies in the antibody screening are based on the higher sensitivity of the Immucor Capture solid phase technology. This benefit is accompanied on other hand by a higher expenditure of time and effort for antibody identification or the verification of false-positive reactions in the initial antibody search [17][18][19]. The advantage of all systems like the Immucor Galileo is the system and process stability and the concordance with the given standard operating procedures according to the demands of GLP and the data security with automated reading, positive sample and reagent identification, positive cassette identification, reaction grading and interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…antibody screening, cross match, etc.) [17,18]; also gel card agglutination technique screening for the detection of feto-maternal haemorrhage (detection of small subpopulation of fetal D-positive cells in maternal sample) has been published [19].…”
Section: Transfusion Medicine-immunohaematologic Investigationsmentioning
confidence: 99%